A Study on Consumer Preferences of Students within the University Belt Area as one factor in setting - up ihaw-ihaw quick - serve restaurant. - 4 0 16; 5
u
Research Paper (BSBA major in Entrepreneurship) Pamantasan ng Lungsod ng Maynila, 2013.
Keywords: 2 -- 0; 6; 20; 20; 2